Association of single nucleotide polymorphisms in AXIN2, BMP4, and IRF6 with Non-Syndromic Cleft Lip with or without Cleft Palate in a sample of the southeast Iranian population - Houshang Rafighdoost; Mohammad Hashemi; Hiva Danesh; Fatemeh Bizhani; Gholamreza Bahari; Mohsen Taheri
Abstract Non-syndromic cleft lip with or without palate (NSCL/P) is a common congenital malformation worldwide, with complex etiology. It has been proposed that interaction of genes and environmental factors play a role in the predisposition to this disease. Objectives: The aim of this study was to examine the association between AXIN2 (axis inhibition protein 2) rs7224837, BMP4 (bone morphogenetic protein 4) rs17563, and IRF6 (interferon regulatory factor 6) rs861019 and 2235371 polymorphisms and NSCL/P in an Iranian population. Material and Methods: This case-control study was carried out on 132 unrelated NSCL/P patients and 156 healthy subjects. The variants were genotyped using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Results: The findings suggest that BMP4 rs17563 polymorphism significantly decreased the risk of NSCL/P in codominant (OR=0.36, 95%CI=0.17-0.79, p=0.012, CT vs CC and OR=0.11, 95%CI=0.01-0.88, p = 0.019, TT vs CC), dominant (OR=0.30, 95%CI=0.15-0.62, p = 0.0007, CT+TT vs CC), recessive (OR=0.12, 95%CI=0.02-0.99, p = 0.023, TT vs CC+CT), overdominant (OR=0.39, 95%CI = 0.18-0.84, p=0.021, CT vs CC+TT), and allele (OR=0.28, 95%CI=0.15-0.55, p<0.0001, T vs C) inheritance models. Our findings did not support an association between AXIN2 rs7224837 and IRF6 rs861019 polymorphism and risk/protection of NSCL/P. The IRF6 2235371 variant was not polymorphic in our population. Conclusion: The results indicate that the BMP4 rs17563 variant is likely to confer a protective effect against the occurrence of NSCL/P in a sample of the southeast Iranian population.